SENIOR CITIZENS IN INDIA – A CRITICAL ANALYSIS OF THE MWPSC ACT, 2007 - Lata, Aman; Jilova, Dr. C.R. (International Journal of Research -GRANTHAALAYAH, 2026)
Presently, the Maintenance and Welfare of Parents and Senior Citizens Act, 2007 is playing a very important role in protecting and promoting the welfare, dignity and wellbeing of the elderly parents and senior citizens of India. The Act provides a comprehensive and exclusive legal framework for securing the financial, health, shelter, maintenance and property rights of the elderly people and fills the vacuum and defects of other legal provisions protecting the maintenance right of senior citizens. Despite being a Comprehensive Act for the wellbeing of the senior citizens, with the passage of time, many shortcomings have been revealed in this specific Act, 2007 because of which the Ministry of Social Justice and Empowerment came forward with some recommendations under the “Maintenance and Welfare of Parents and Senior Citizen (Amendment) Bill, 2019. But unfortunately, the Bill still is waiting for its approval in our Parliament. This Article critically analysis the major provisions of the Act, 2007 and the Bill, 2019 along with the role of Indian Judiciary for the effective implementation of the Act, 2007 and the right of our parents and senior citizens.